Inconsistencias en la afiliación al sistema de salud colombiano: barrera administrativa para la atención integral de las urgencias médicas (2014)
ABSTRACT: To explore the healthcare provided for medical emergencies to patients with inconsistencies in their affiliation with the General System of Social Health Security (gsshs) in various Health Providing Institutions (hpi) of Medellin in 2012. Methodology: we conducted a qualitative study using Grounded Theory. Twenty semi-structured interviews were applied to healthcare professionals working at emergency departments and to patients with inconsistencies in their gsshs affiliation. Results: there is non-compliance with the regulations governing the provision of emergency services, which turns the administrative processes into barriers preventing access to the system and for providing healthcare in medical emergencies; this ultimately results in a lack of comprehensive healthcare. Conclussion: It is therefore necessary that the gsshs monitoring organizations ensure compliance with the current regulations. Likewise, a change in the legislation is required to bridge the legal gaps as well as a transformation in the way in which the citizens affiliate with the health system. Such transformation should also guarantee universal access and comprehensive care and must be independent from the stability of work relationships.